Exploring the relationship between media use and depressive symptoms among gender diverse youth: findings of the Mental Health Days Study - Diana Klinger; Paul L. Plener; Golli Marboe; Andreas Karwautz; Oswald D. Kothgassner; Tobias Dienlin (BMC, 2024)
Abstract Background Over the past decades, media use has become a key aspect of young people's daily lives, significantly shaping their social interactions, learning processes, and recreational pursuits. At the same time, healthcare professionals and researchers are increasingly concerned about the impact of media use on young people's mental health. This concern is particularly relevant for gender diverse youth who may have distinct experiences with media that could impact their mental health uniquely compared to their peers, such as increased exposure to cyberbullying and negative content regarding their gender identity. This study aims to explore the associations between media use and depressive symptoms among youth and examine if gender moderates this association. Methods This study utilized a cross-sectional design involving a school-based sample of 8158 participants (M age = 14.05 years, SD = 2.45, N diverse = 144) from Austria. Participants completed a survey assessing their media use and depressive symptoms using the Patient Health Questionnaire-9 (PHQ-9). Media use was measured by asking participants to report their daily usage in hours and minutes across various categories, including smartphone use, streaming services, social networks, and other media types. Multiple regression analyses were conducted to examine relationships between different forms of media use and depressive symptoms. Moderation analyses were performed using the PROCESS macro for SPSS to explore the role of gender. Results For gender diverse youth, multiple regression analysis identified streaming services (β = 0.265, p = .005) and social networks (β = 0.189, p = .037) as significant predictors of depressive symptoms in gender diverse youth. Moderation analyses conducted with the entire sample showed that gender moderates the relationship between depressive symptoms and smartphone use (B = - 0.008, p = .014), with the effect being the most negative for gender diverse individuals. Conclusion The findings underscore the complex relationship between media use and depressive symptoms among gender diverse youth, emphasizing the moderating role of gender. These results underline the need for gender-sensitive approaches in media literacy and mental health interventions. Stakeholders should be aware of risks and benefits of different media types to foster healthy media engagement.